The Effectiveness of PAI Learning Innovation through Game Integration and Ice Breaker according to the principal of SMAN Central of Lombok - Hidayatullah, Syarif; Muhammad, Muhammad; Idrus, S. Ali Jadid Al (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyze the effectiveness of Islamic Religious Education (PAI) learning innovations through the integration of games and ice breakers in State High Schools of Central Lombok Regency. By adopting a qualitative approach, this research involves in-depth interviews with school principals as well as observations on the implementation of these innovations in the classroom. The results show that the integration of games and ice breakers in PAI learning not only increases students' interest and motivation, but also creates a more interactive and fun learning atmosphere. The principal stated that this innovation has succeeded in reducing student boredom in the learning process and increasing their engagement. In addition, the results of the evaluation showed a significant increase in understanding of the teaching material. This study recommends the application of similar innovations in other schools to improve the quality of PAI learning.